2021
DOI: 10.33902/jpr.2021167935
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of classroom teachers on the homework process in teaching mathematics: An interpretative phenomenological analysis

Abstract: This phenomenological study aimed to explore a group of classroom teachers' experiences with homework assignment in teaching mathematics. The participants of the study were 27 classroom teachers who were selected using the criterion-based sampling technique. The research data were collected with a semi-structured interview form developed by the researchers and subjected to interpretive phenomenological analysis. The results showed that the teachers plan the homework they would assign the evening before the cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…The present study revealed that teachers assign a few questions as HW on a daily basis as they do not want to burden and demotivate the students by giving too many questions, and students are expected to complete the task within an hour. This finding is similar to the findings of Ergen & Durmuş , who reported that teachers focused on assigning HW that took less than an hour so that the students would not be discouraged [15]. Nevertheless, in the context of this study, the number of hours spent by the students might be higher than what is mentioned by the teachers.…”
Section: Homework Managementsupporting
confidence: 90%
See 4 more Smart Citations
“…The present study revealed that teachers assign a few questions as HW on a daily basis as they do not want to burden and demotivate the students by giving too many questions, and students are expected to complete the task within an hour. This finding is similar to the findings of Ergen & Durmuş , who reported that teachers focused on assigning HW that took less than an hour so that the students would not be discouraged [15]. Nevertheless, in the context of this study, the number of hours spent by the students might be higher than what is mentioned by the teachers.…”
Section: Homework Managementsupporting
confidence: 90%
“…Most of the teachers believed that it was not possible to assess every student's HW because of time constraints. A similar conclusion was drawn by the findings of Ergen and Durmuş who found that some teachers only checked whether the students had done the homework or not since the feedback process took a lot of time [15]. However, the concern here is that students won't be able to correct their mistakes if the assessment is not done, which could result in incorrect learning.…”
Section: Homework Managementsupporting
confidence: 75%
See 3 more Smart Citations